EKSPERIMENTASI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) DENGAN METODE DISCOVERY LEARNING PADA MATERI POKOK BENTUK ALJABAR DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS - Jamilah Jamilah (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of this research was to reveal the effect of PMR approach with discovery learning method, PMR approach, and directed instruction approach to the mathematics achievement in Algebra Expression viewed from mathematics communication ability. The type of this research was a quasi experimental by 3x3 factorial design. The population in this research was the seventh grade students of junior high school in Pontianak in the academic year 2012/2013. The total of sample was 9 classes and it was taken using stratified cluster random sampling technique. The instrument of research using mathematics achievement test and mathematics communication ability test. The data was analyzed using unbalanced two-way analysis of variance. The conclusion of this research shows that PMR approach with discovery learning method, PMR approach and directed instruction approach give the same mathematics achievement and it shows the same result in each level of mathematics communication ability. Other conclusion also shows that the students who have high mathematics communication ability have better mathematics achievement than the students who have middle or low mathematics communication ability, the students who have middle mathematics communication ability have better mathematics achievement than the students who have low mathematics communication ability, and it shows the same result in each learning approach categories.Key words: PMR Approach, Discovery Learning Method, Directed Instruction Approach, Mathematics Communication Ability, Mathematics Achievement.